KLEPTOMANIA AND ATTENTION DEFICIT HYPERACTIVITY DISORDER- CASE REPORT - Ayyildiz Didem (Sanamed, 2018)
Kleptomania as a type of impulse control disorder (ICD) characterized by an inability to resist urges to steal objects not valuable or needed for personal use. Kleptomania may co-occurs with many psychiatric disorders frequently other impulse control disorders, obsessive-compulsive disorder, anxiety disorders, affective disorders, eating disorders and substance use disorders. We presented two adolescent cases admitted to Marmara University Child and Adolescent Psychiatry outpatient clinic because of stealing behavior and diagnosed with Kleptomania and ADHD. Both cases had improvement in stealing behavior after ADHD treatment. Careful monitoring of comorbid conditions in the psychiatric evaluation of Kleptomania cases is very important in terms of treatment and prognosis.